Energia eólica no Brasil: a contribuição do Nordeste e do Rio Grando do Norte na diversificação da matriz energética - Maria Eduarda Medeiros da Silva; José Alderir da Silva (Revista de Economia Mackenzie)
Diversifying the energy matrix involves using multiple sources to generate electricity for a nation. This approach is crucial to ensure that the population and the country are prepared to face potential crises in one of the energy sources, as there will be others available to meet energy needs. The Brazilian energy matrix features a wide variety of energy sources, considered one of the cleanest in the world due to the significant contribution of renewable sources, such as wind energy. Thus, the objective of this article is to analyze the process of diversifying the country’s electrical matrix and the role of wind energy in this process. Therefore, the research will highlight the advantages and disadvantages of the Brazilian energy matrix while emphasizing the importance of diversification for the country and the complementary role of wind energy in relation to hydroelectric power. The adopted method will be a qualitative analysis using a deductive strategy, starting with a general analysis of the world, Brazil, the Northeast region, and finally, Rio Grande do Norte. Thus, it moves from a broad analysis to a specific examination regarding the process of diversifying the country’s electrical matrix.